1996
DOI: 10.1016/0277-9536(95)00190-5
|View full text |Cite
|
Sign up to set email alerts
|

Explaining urban-rural variations in health: A review of interactions between individual and environment

Abstract: In order to gain insight into the relation between health and people's environment, literature published between 1985 and 1994 was gathered from several international databases. An introduction into existing theory regarding geographic disparities is presented: geographical drift and breeder hypotheses are discussed. This is followed by a critical review focusing on interaction effects of urbanicity and individual characteristics on health. This leads to two major conclusions. First, emphasis in past research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
1
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(115 citation statements)
references
References 59 publications
4
107
1
3
Order By: Relevance
“…Therefore, we cannot ignore the possibility that the amount of greenspace is`simply' a new indicator for level of urbanity. This would imply that the relationship between greenspace and health might be explained by the same mechanisms as suggested for the relationship between urbanity and health, for example, a less healthy lifestyle in more urban areas (Verheij, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we cannot ignore the possibility that the amount of greenspace is`simply' a new indicator for level of urbanity. This would imply that the relationship between greenspace and health might be explained by the same mechanisms as suggested for the relationship between urbanity and health, for example, a less healthy lifestyle in more urban areas (Verheij, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…For this indicator, the municipal level was considered to be more appropriate than that of neighbourhoods, because household density was meant as an indicator not only of an urban physical environment, but also of an`urban' style of life. An`urban' lifestyle is generally regarded as an important factor in explaining rural^urban differences in health (Verheij, 1995).…”
Section: Characteristics Of People's Living Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these associations are complex, only occurring within certain groups. For example, urbanity (Verheij, 1996) and socio-economic status (Weich & Lewis, 1998a) has been found to predict mental health particularly for women and the elderly.…”
Section: Mental Healthmentioning
confidence: 99%
“…Urban-rural disparities are a major field of study in public health, in both the developed and developing worlds, and studies have reported both positive and negative health outcomes with urban living (Galea & Vlahov, 2005;McDade & Adair, 2001;Sobngwi, Mbanya, Unwin, Porcher, Kengne, Fezeu et al, 2004;Torun, Stein, Schroeder, Grajeda, Conlisk, Rodriguez et al, 2002;Verheij, 1996). In these analyses we utilize a multidimensional measure designed specifically for the CHNS to capture urbanization from the physical, social, cultural, and economic environments (Mendez & Popkin, 2005).…”
Section: Community Level Variablementioning
confidence: 99%